INCREASING CASSAVA JERKY PROTEIN THROUGH THE FERMENTATION PROCESS USING SACCHAROMYCES CEREVISIAE AND RHIZOPUS ORYZAE - Nurhayati, Anis Anis; Khurniyati, Maylina Ilhami; Nisak, Yunita Khilyatun (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
Cassava is a plant that is easy to grow in Indonesia. People generally use cassava as a food source of carbohydrates, while the leaves are used as a vegetable by processing it into curry or stir-fry. Cassava leaves have high nutritional value but have yet to be used optimally; most become agricultural waste. This study aims to increase cassava leaf jerkys nutritional value (protein) using microbial fermentation. The experimental design used in this study was a factorial, Completely Randomized Design with two factors: the type of microbe (Saccharomyces cerevisiae, Rhizopus oryzae) and fermentation time (2, 3, 4 and 5 days). The parameters analyzed were protein content, ash content, fat content, carbohydrate content, water content and consumer preference level. From the results of this study, there was an increase in protein levels in cassava leaves for up to 120 hours (5 days), 15.395% using Saccharomyces cerevisiae and 16.165% using Rhizopus oryzae. The ash content significantly differs from treatments with shorter fermentation times of 96 hours, 72 hours or 48 hours. There is no significant difference in the percentage of water content in the various treatments between the treatments. The highest score in the organoleptic test is A2B4 (jerky with the addition of Rhizopus oryzae with a fermentation time of 120 hours).